(untitled) (Geologica Macedonica, 2015)
The distribution of lead, which in higher content represents hazard to the environment, causescertain unwanted consequences on human health. Therefore, the environmental monitoring not only for the lithogenicbut also for the anthropogenic distribution leads to determination of the main hot spots in the environment. Bregalnicariver basin in the Republic of Macedonia was selected as a study area with the presence of three potential emissionsources: lead and zinc mines (“Zletovo” and “Sasa” mines) and copper mine (Bučim mine). The lead contents inalluvial and automorphic soil range from 4.4 to 46000 mg kg-1. The most enriched subarea with lead in the Bregalnicariver basin is the Zletovo–Kamenica region. The average Pb content in these subareas is 3100 mg kg–1. Despite theanthropogenic activities in the above mentioned mines, enriched Pb deposition in soil is mainly correlated with thedominant geological formations, such as Neogene pyroclastites and vulcanites and Proterozoic gneisse and shales.